2022
DOI: 10.31124/advance.20330850.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Work Diversity on Organizational Performance in the Hospitality Sector in the UAE: The Moderating Role of HR Practices

Abstract: <p>The structure of workplace in hospitality sector has become apparently diverse. As a vital step in defining how diversity affects organizational performance, we suggested training as a mediator over which diversity in income level and race indirectly affects organizational performance. We also emphasized two human resource practices, namely, rewards and performance appraisal, as important possibilities that moderate the impact of employee diversity on training and organizational performance.  A sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Their research demonstrated that contingent rewards boost performance. This conclusion was consistent with others (Khassawneh and Mohammad, 2022b;Yukl, 1994;Bass, 1990a) that linked contingent reward to subordinates' performance and satisfaction. No empirical study has been provided on the association between transformative leadership and service quality.…”
Section: Transformational Leadership and Performancesupporting
confidence: 91%
“…Their research demonstrated that contingent rewards boost performance. This conclusion was consistent with others (Khassawneh and Mohammad, 2022b;Yukl, 1994;Bass, 1990a) that linked contingent reward to subordinates' performance and satisfaction. No empirical study has been provided on the association between transformative leadership and service quality.…”
Section: Transformational Leadership and Performancesupporting
confidence: 91%
“…It is up to the respondent to determine what constitutes a change; however, the standard procedure is to inquire about ways in which existing tools could be (considerably) enhanced. If these companies have made adjustments and enhancements to their HR management, policies, and practices, then they are considered innovative (Khassawneh & Mohammad, 2022a).…”
Section: Fairness In Treatment Investment In People Possibility Of Lo...mentioning
confidence: 99%
“…Their cultural backgrounds may shape people’s self-perceptions of their emotional intelligence and outward displays of emotion. Self-reported emotional Intelligence (EI) may, for instance, be influenced by social norms regarding what kinds of emotions are deemed appropriate [ 59 , 75 ]. An extraordinarily expressive and extroverted person would rate themselves lower in expressive control if raised in a culture that valued emotional repression and a calm demeanor.…”
Section: Resultsmentioning
confidence: 99%